Long-Term Results of Stenting of Left Main Coronary Artery Lesions: Experience of One Hospital - Olena V. Levchyshyna; Sergii V. Salo; Yevhenii V. Aksonov (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To study the effectiveness of left main coronary artery (LMCA) stenting in patients with coronary heart disease and to optimize the choice of percutaneous coronary intervention technique based on the experience of one clinic.Materials and methods. The study, which was conducted at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine, included 107 patients with LMCA disease, who underwent stenting from January 2019 to December 2023. During the study, the patients were divided into two groups. One group underwent stenting using the single-stent method (44 patients, 41.1%), while the other group underwent stenting using the double-stent method (63 patients, 58.9%).Results. In the group of surveyed patients after stenting, an analysis was conducted regarding adherence to drug therapy and achievement of target lipid spectrum levels. It was found that one of the reasons for the active progression of atherosclerosis can be considered low adherence to drug therapy. A group of patients with recurrence of angina after stenting, the cause of which was restenosis in the stented segment, was analyzed. In the analysis of the frequency of repeated interventions in patients with hemodynamically significant lesions of the LMCA, who initially underwent stenting, it was found that 24.5% of patients (n = 24) underwent stenting again at the second visit and only 4 patients (4.1%) underwent bypass surgery, which is statistically significant (p ≤ 0.001).Conclusions. LMCA stenting is an effective way of treating patients with hemodynamically significant damage to it (effectiveness of the technique is 71.4%). Recurrence of angina was observed in 28 patients (28.6%). Both single-stent and double-stent procedures are effective: recurrence of angina was observed in 13.3% and 15.3% of cases, respectively. One of the main reasons for the recurrence of angina pectoris is the progression of atherosclerosis in new locations (39.3%) and restenosis in stenting segment (39.3%).